Gender Bias and Feminist Exegetical Critique of the YouTube Channel @gurugembul - Melani Novita Anggraini (Journal of Islamic Thought and Contemporary Studies, 2025)
Gender bias in leadership has become an important issue in public discourse, especially in relation to Guru Gembul's statement on his YouTube channel that the differences in the leadership styles of Sri Mulyani and Purbaya are due to gender. The main problem that arises is the public's tendency to accept this view without realizing that it represents gender bias that continues to be produced through digital media. This study aims to correct this understanding based on the gender interpretations of Husein Muhammad and Faqihuddin Abdul Kodir, so that gender bias does not become more widespread in society. The method used is a comparative study of the interpretations of the two scholars, using an interpretive and gender analysis approach. The results of the study show that the assumption of the natural superiority of men contradicts the character of the language of the Qur'an according to Husein Muhammad, while QS. An-Nisā': 34 according to Faqihuddin Abdul Kodir does not reject the involvement of women in leadership as long as they have adequate capacity and competence. In conclusion, leadership should be understood contextually and based on the principle of maṣlaḥah ‘āmmah, emphasizing public interest, cooperation, and gender equality. An important implication of this study is that public discourse and digital content can be corrected through fair interpretation, opening up equal opportunities for women and men in leadership.